The Song of Macapat Semarangan: The Acculturation of Javanese and Islamic Culture - Cahyono, Agus; Widodo, Widodo; Jazuli, Muhamad; Murtiyoso, Onang (Harmonia: Journal of Arts Research and Education, 2020)
The research objective is to explain the macapat Semarangan song which is the result of acculturation of Javanese and Islamic culture. The study used qualitative methods by uncovering the concept of processing of Javanese music and acculturation. Research location was in Semarang with the object of macapat Semarangan song study. Data was collected through interviews, observations, and study documents. The validity of the data was examined through triangulation techniques and the analysis is done through the stages of identification, classification, comparison, interpretation, reduction, verification, and making conclusions. The results showed that the macapat Semarangan song has unique characteristics of arrangement. The song’s grooves use long and complicated musical ornamentations with varying pitch heights to reach high notes. This is a manifestation of the results of acculturation of Javanese and Islamic culture seen from arrangement on the parts of Adzan (call to prayer) and tilawatil Qur’an. The process of acculturation of elements of Islamic culture also involves scales. Azan songs use diatonic scales, some macapat Semarangan songs also use the same scales, but a cycle of five notes close to nuances of Chinese music scales. Various elements of arrangement on the Azan, Chinese and European musical scales then formed a new culture, macapat Semarangan.